Saxifraga granulata (Saxifragaceae) в Україні - Мельник, В.І.; Баранський, О.Р.; Володимирець, В.О.; Логвиненко, І.П.; Гуцман, С.В. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2014)
Saxifraga granulata L. — редкий вид флоры, который в Украине находится на восточной границе ареала. Изучено географическое распространение, условия местопроизрастания и состояние популяций Saxifraga granulata в Украине. Описаны новые местонахождения вида в Ровенской и Волынской областях. Saxifraga granulata L. in Ukraine is at the eastern border of its range. The geographical distribution, habitats conditions and population state of S. granulata in the country were studied. New localities of the rare species from Rivne and Volyn Regions are reported and described.